Supplementation with fish oil reduces αβ 42 burden and shifts αβ precursor protein processing toward non-amyloidogenic pathways in a rat model of hyperglycaemic Alzheimer’s disease. - Titisari, Nurina; Fauzi, Ahmad; Abdul Razak, Intan Shameha; Samsulrizal, Nurdiana; Ahmad, Hafandi (Cambridge University Press, 2025)
This study examines the influence of fish oil on brain amyloidogenesis in hyperglycaemic Alzheimer’s disease animal models, emphasising the potential of omega-3 fatty acids in fish oil to prevent the development of Alzheimer’s disease. Thirty males of Wistar rats were divided into five groups: 1) control rats (NS); 2) rats supplemented with 3 g/kg of fish oil (NSþFO3); 3) rats injected via intraperitoneal (i.p) with Streptozotocin-Lipopolysaccharide (STZ-LPS); 4) rats injected with STZ-LPS (i.p) and supplemented with 1 g/kg of fish oil (STZ-LPSþFO1), and 5) rats injected with STZ-LPS (i.p) and supplemented with 3 g/kg of fish oil (STZ-LPSþ FO3). The cerebral brain was extracted for examination, and the αβ precursor protein (APP) level was measured using an immunoassay kit, while αβ 42 expression was evaluated using immunohistochemistry staining. Brain amyloidosis-related genes were quantified using real-time Polymerase Chain Reaction (PCR). The results revealed that fish oil supplementation significantly increased APP levels and reduced αβ 42 accumulations in STZ-LPS rats. Moreover, the Apolipoprotein E, ε4 isoform (ApoE-4) and Beta-site APP-cleaving enzyme 1 (Bace-1) genes were downregulated while the Low-density lipoprotein receptor-related protein 1 (Lrp-1) gene was upregulated in STZ-LPS rats treated with fish oil, thereby elucidating the impact of fish oil on diminishing αβ buildup in the brain. Therefore, this study contributes to a growing body of evidence supporting dietary interventions as adjunctive strategies for the prevention or delay of Alzheimer’s disease progression in metabolic dysfunction.